P144 Validation of the Musculoskeletal Health Questionnaire (MSK-HQ) in patients with musculoskeletal pain in primary care. (20th April 2020) - Scott, Ian C; McCray, Gareth; Lancaster, Gillian; Foster, Nadine E; Hill, Jonathan C
Abstract: Background: The Musculoskeletal Health Questionnaire (MSK-HQ) is a recently developed generic patient-reported outcome measure (PROM), evaluating impacts of musculoskeletal (MSK) conditions on patients' health. Its scores range 0-56; higher scores indicate better health. Its performance (a) in patients with MSK-pain in primary care, and (b) compared to MSK pain-site reference PROMs, is uncertain. We addressed these uncertainties through secondary analysis of a previous primary-care based study, enrolling 524 patients with shoulder, neck, lower back, knee, or multi-site MSK pain managed by GPs, from 8 West Midlands practices. Methods: The study captured the following self-report questionnaire data at 0 and 6 months: MSK-HQ, EQ-5D-5L, Roland-Morris Disability Questionnaire (back pain), Neck Disability Index (neck pain), Shoulder Pain and Disability Index (shoulder pain), Knee Injury and Outcome Score (knee pain), Short-Form-12 (multisite pain). At 6 months, patients self-rated their global change in MSK pain, from -5 ("very much worse") to + 5 ("completely recovered"). Receiver operating characteristic curves evaluated the ability of 6-month changes in each PROM to discriminate between patients improving/not improving on global change scores. Minimal Clinically Important Differences (MCID) were calculated (cut-off optimising discriminatory sensitivity/specificity). Results: Most (60%) reported pain improvements, with mean baseline MSK-HQ scores rising from 29.4 to 37.4 over 6-months. The MSK-HQ had a moderate ability to discriminate between patients improving vs. no change/worsening in MSK pain (area under the curve [AUC] 0.81; 95% CI 0.78-0.85). Its discriminative ability was better than the EQ-5D-3L (AUC 0.68; 95% CI 0.62-0.73) and at least as good as site-specific PROMs (Table). MCID for the 6-month change in MSK-HQ was 5.5 across all patients. Minor variation (<2.0 units) was observed in MSK-HQ MCID across 4/5 pain sites. The MSK-HQ had strong correlations with all PROMs except SF-12 physical/mental component summary scores. Conclusion: In patients consulting in primary care with MSK pain, the MSK-HQ appears at least as good as existing pain-site specific PROMs at identifying patients self-reporting pain improvements, and superior to the EQ-5D-5L. Our results support the use of the MSK-HQ in this setting. Disclosures: I.C. Scott None. G. McCray None. G. Lancaster None. N.E. Foster None. J.C. Hill None.